Assemblage structure and secondary production of mesozooplankton in shallow water volcanic CO2 vents of the Azores - Campoy, Ana Navarro (2015)
Dissertação de mestrado, Biologia Marinha, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2015 Atmospheric CO2 concentrations have increased by at least 30% since pre-industrial times due to human activities. Part of this CO2 has been absorbed by oceans, inducing ocean acidification and, therefore, several impacts in the marine biota. Natural shallow-water CO2 vents have generated a substantial interest in recent years as in situ laboratories for ocean acidification studies. The present study was focused on the effects of ocean acidification on mesozooplankton communities. Two active volcanic areas with submarine CO2 emissions, in the islands of São Miguel and Faial, were chosen and independently studied, through the choice of three different sites: Reference, Intermediate and Vent, characterized for their increase in the CO2 degassing activity, and consequent pH decrease. Differences in the abundance, diversity and structure of mesozooplankton among sites were described, along with the characterization of the community in these areas, since previous information is scarce. Differences were found in the composition of the zooplanktonic assemblages among sites in São Miguel and among dates in Faial. Through the nMDS analyses, Radiozoa, Paracalanus parvus and Evadne spinifera appeared more related to vent conditions, while Cirripedia nauplii were closer to the reference conditions. Conditions in Faial did not allow a clear separation among sites in the nMDS analyses, since the strong currents mix the water, dissipating the effect of the gas emissions, and variation among days becomes more important and statistically significant. The RNA:DNA ratio of selected mesozooplankton populations was used, as proxies for physiological condition. RNA:DNA did not show a clear pattern of variation, copepods in São Miguel and cladocerans in Faial had an higher ratio in the reference sites, but with no gradual decrease to the Vent. Fish eggs seem to have an inverted pattern. Additional experiments conducted under ...